2017
DOI: 10.1093/infdis/jix291
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Metabolic Stress Disrupts Immune Homeostasis and Induces Proinflammatory Responses in Human Immunodeficiency Virus Type 1– and Combination Antiretroviral Therapy–Exposed Infants

Abstract: SummaryHere, we show that the mitochondrial and lipid metabolism in uninfected infants born to HIV-1–infected women and with prenatal exposure to combination antiretroviral therapy is dysregulated and is associated with enhanced immune activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 49 publications
1
29
0
1
Order By: Relevance
“…Posaconazole resistance in A. terreus was newly detected in a few isolates; however, these isolates were collected between 2007 and 2009. Some countries report an alarmingly increase of antifungal resistance development within the past, with azole-resistant A. fumigatus displaying the major threat [ 4 ]. In Tyrol, fungal in vitro susceptibility data have not changed tremendously; conspicuous trends were not observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Posaconazole resistance in A. terreus was newly detected in a few isolates; however, these isolates were collected between 2007 and 2009. Some countries report an alarmingly increase of antifungal resistance development within the past, with azole-resistant A. fumigatus displaying the major threat [ 4 ]. In Tyrol, fungal in vitro susceptibility data have not changed tremendously; conspicuous trends were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Azole antifungal drugs are the first line of therapy against A. fumigatus , a common etiologic agent of aspergillosis [ 8 ]. Resistance to azole drugs has been associated with treatment failure and deaths in patients with aspergillosis [ 4 ]. However, azole resistance in A. fumigatus has been documented in many regions in the past decade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Viral particles including HIV are known to induce the production and activate complement C3 ( 33 35 ). Also, studies showed that fetal exposure to HIV and ART skews newborns infant’s physiological immune responses toward inflammation ( 36 ). Therefore, HEU infants in utero exposure to HIV particles and pro-inflammatory environment ( 37 ) could explain the higher level of complement C3 found in HEU infants.…”
Section: Discussionmentioning
confidence: 99%